Reconstruction of the Origin of a Neo-Y Sex Chromosome and Its Evolution in the Spotted Knifejaw, Oplegnathus punctatus. (9th March 2021) - Li, Ming; Zhang, Rui; Fan, Guangyi; Xu, Wenteng; Zhou, Qian; Wang, Lei; Li, Wensheng; Pang, Zunfang; Yu, Mengjun; Liu, Qun; Liu, Xin; Schartl, Manfred; et al.
Abstract: Sex chromosomes are a peculiar constituent of the genome because the evolutionary forces that fix the primary sex-determining gene cause genic degeneration and accumulation of junk DNA in the heterogametic partner. One of the most spectacular phenomena in sex chromosome evolution is the occurrence of neo-Y chromosomes, which lead to X1X2Y sex-determining systems. Such neo-sex chromosomes are critical for understanding the processes of sex chromosome evolution because they rejuvenate their total gene content. We assembled the male and female genomes at the chromosome level of the spotted knifejaw ( Oplegnathus punctatus ), which has a cytogenetically recognized neo-Y chromosome. The full assembly and annotation of all three sex chromosomes allowed us to reconstruct their evolutionary history. Contrary to other neo-Y chromosomes, the fusion to X2 is quite ancient, estimated at 48 Ma. Despite its old age and being even older in the X1 homologous region which carries a huge inversion that occurred as early as 55–48 Ma, genetic degeneration of the neo-Y appears to be only moderate. Transcriptomic analysis showed that sex chromosomes harbor 87 genes, which may serve important functions in the testis. The accumulation of such male-beneficial genes, a large inversion on the X1 homologous region and fusion to X2 appear to be the main drivers of neo-Y evolution in the spotted knifejaw. The availability of high-quality assemblies of the neo-Y and both X chromosomes make this fish an ideal model for a better understanding of the variability of sex determination mechanisms and of sex chromosome evolution.